(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
By observation on life-cycle of Bactrocera oleae Gmelin (Diptera Tephritidae) on fruits of Olea europaea var. sylvestris Brot. in field, the Authors ascertained this insect performs two generations during spring time. The following list of natural enemies were also found: Asecodes erxias (Walker), Pnigalio agraules (Wlk.) (Eulophidae), Eupelmus urozonus Dalm. (Eupelmidae), Hobbya sp. (Pteromalidae), Psyttalia concolor (Szepligeti) (Braconidae), Prolasioptera berlesiana Paoli. The highest percentage of parasitism was performed by P. agraules (37.68%) over an average total of 42% about due to all species of parasitoids, followed from those ones of A. erxias and P. concolor.